Recent Advances in Polymer-Based Vaginal Drug Delivery Systems - Tomasz Osmałek; Anna Froelich; Barbara Jadach; Adam Tatarek; Piotr Gadziński; Aleksandra Falana; Kinga Gralińska; Michał Ekert; Vinam Puri; Joanna Wrotyńska-Barczyńska; Bozena Michniak-Kohn (MDPI AG, 2021)
The vagina has been considered a potential drug administration route for centuries. Most of the currently marketed and investigated vaginal formulations are composed with the use of natural or synthetic polymers having different functions in the product. The vaginal route is usually investigated as an administration site for topically acting active ingredients; however, the anatomical and physiological features of the vagina make it suitable also for drug systemic absorption. In this review, the most important natural and synthetic polymers used in vaginal products are summarized and described, with special attention paid to the properties important in terms of vaginal application. Moreover, the current knowledge on the commonly applied and innovative dosage forms designed for vaginal administration was presented. The aim of this work was to highlight the most recent research directions and indicate challenges related to vaginal drug administrations. As revealed in the literature overview, intravaginal products still gain enormous scientific attention, and novel polymers and formulations are still explored. However, there are research areas that require more extensive studies in order to provide the safety of novel vaginal products.